Impact of Industry 4.0 on sustainable tourism : perspectives, challenges and future - Tucková, Zuzana; Dey, Sandeep Kumar; Thai, Hoc Huynh; Hoang, Sinh Duc (Emerald Publishing Limited, 2023)
The tourism and hospitality industry is at the forefront of the climate crisis as a significant source of carbon emissions on a global scale. There is a need to disseminate opportunities and explore scientific avenues in emerging technologies associated with industry 4.0 , such as artificial intelligence, virtual and augmented reality, 'extended reality' or the use of service robots, and forecasting future trends in the tourism industry's fight against the climate crisis. Translating these current and future problems into pragmatic solutions, the chapter authors explore the opportunities for both academia and industry in agile and disruptive technologies. By integrating unique features of these advancements like Extended Reality (XR), Machine Intelligence (MI) and Computer Vision (CV), Impact of Industry 4.0 on Sustainable Tourism determines the trajectory of sustainable tourism development. Of interest to both academics and practitioners, Impact of Industry 4.0 on Sustainable Tourism reveals patterns and projections to provide a discourse on the progression of disruptive and futuristic technologies in the field of sustainable tourism research and practice.